2013
DOI: 10.1111/nyas.12134
|View full text |Cite
|
Sign up to set email alerts
|

Control of inflammatory heart disease by CD4+ T cells

Abstract: This review focuses on autoimmune myocarditis and its sequela, inflammatory dilated cardiomyopathy (DCMI), and the inflammatory and immune mechanisms underlying the pathogenesis of these diseases. Several mouse models of myocarditis and DCMI have improved our knowledge of the pathogenesis of these diseases, informing more general problems of cardiac remodeling and heart failure. CD4(+) T cells are critical in driving the pathogenesis of myocarditis. We discuss in detail the role of T helper cell subtypes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 184 publications
(339 reference statements)
1
29
0
Order By: Relevance
“…This effect may be of particular relevance in the clinical setting as increasing evidence indicates that although Th17 cells, and in particular IL-17A, have only a mild effect on the severity of myocarditis during the acute phase in which the major role seems to be played by the Th1 cell [2,4], however they are essential for the long-term progression to DCM [5,6]. In fact, it has been demonstrated that IL-17A-deficient mice, while developing myocarditis with similar incidence and severity to wild-type controls, were protected from postmyocarditis remodelling and did not develop DCM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may be of particular relevance in the clinical setting as increasing evidence indicates that although Th17 cells, and in particular IL-17A, have only a mild effect on the severity of myocarditis during the acute phase in which the major role seems to be played by the Th1 cell [2,4], however they are essential for the long-term progression to DCM [5,6]. In fact, it has been demonstrated that IL-17A-deficient mice, while developing myocarditis with similar incidence and severity to wild-type controls, were protected from postmyocarditis remodelling and did not develop DCM.…”
mentioning
confidence: 99%
“…These models have significantly contributed to increase our knowledge of the pathogenesis of the disease, schematically consisting of three phases: (i) an acute phase, characterized by acute injury of the cardiomyocytes induced by virus replication, (ii) a subacute phase, critically driven by a CD4+ T cell-mediated immune response triggered by the exposure of intracellular antigens as a consequence of myocyte injury, and (iii) a chronic phase, characterized by myocardial repair and remodelling, with the possible progression to DCM [1,2,4]. In this scenario, it is widely accepted that the mainstay actor is the T-helper (Th)1 cell, crucially involved in orchestrating the immune response required for the defence of the virus-infected heart, but also responsible for the organ damage [4]. Nevertheless, increasing evidence strongly suggests that also interleukin (IL)-17 producing Th17 cells play a key role in the process, particularly in the progression of myocarditis to DCM [5,6].…”
mentioning
confidence: 99%
“…In this study, we observed a considerable increase in the frequencies and the suppressive function of circulating CD14 + HL-ADR -/low MDSCs in DCM patients compared with healthy controls, indicating the participation of MDSCs in the immunomodulatory process of DCM. Increasing evidence demonstrates that chronic immune activation and systemic inflammation are critical factors in the development of DCM [4]. As a defensive response to the pathogens near or within cardiac myocytes, activated monocytes and lymphocytes migrate to the myocardium [30].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to support a causative role of abnormal circulating T cell activation and chronic autoimmune T cell responses to cardiac self-antigens in the underlying pathophysiology of DCM [4,[32][33][34]. Cuervo et al described that monocytic MDSCs expressing iNOS and Arg-1 are present in heart tissue in the acute phase of Trypanosoma cruzi infections, which have the potential to suppress T lymphocytes present in the infiltrate [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation